Involvement of nitric oxide and caveolins in the age-associated functional and structural changes in a heart under osmotic stress - Arza, Patricia Raquel (2015)
Previous work done in our laboratory showed that water restriction during 24 and 72. h induced changes in cardiovascular NOS activity without altering NOS protein levels in young and adult animals. These findings indicate that the involvement of NO in the regulatory mechanisms during dehydration depends on the magnitude of the water restriction and on age. Our aim was to study whether a controlled water restriction of 1 month affects cardiac function, NO synthase (NOS) activity and NOS, and cav-1 and -3 protein levels in rats during aging. Male Sprague-Dawley rats aged 2 and 16 months were divided into 2 groups: (CR) control restriction (WR) water restriction. Measurements of arterial blood pressure, heart rate, oxidative stress, NOS activity and NOS/cav-1 and -3 protein levels were performed. Cardiac function was evaluated by echocardiography. The results showed that adult rats have greater ESV, EDV and SV than young rats with similar SBP. Decreased atria NOS activity was caused by a reduction in NOS protein levels. Adult animals showed increased cav-1. Water restriction decreased NOS activity in young and adult rats associated to an increased cav-1. TBARS levels increased in adult animals. Higher ventricular NOS activity in adulthood would be caused by a reduction in both cav. Water restriction reduced NOS activity and increased cav in both age groups. In conclusion, our results indicated that dehydration modifies cardiac NO system activity and its regulatory proteins cav in order to maintain physiological cardiac function. Functional alterations are induced by the aging process as well as hypovolemic state.